FAKTOR-FAKTOR YANG MEMENGARUHI PROFITABILITAS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Song, William; Susanto, Liana (Jurnal Paradigma Akuntansi, 2024)
This research aims to obtain empirical evidence regarding the effect of the independent variables of liquidity, leverage, and firm size on the profitability of manufacturing companies listed on the Indonesia Stock Exchange during 2018-2020. This study used 68 manufacturing companies which were selected using purposive sampling method. The data processing technique in this study used the Eviews 12.0 SV program. The results of this study indicate that leverage has a significant positive effect on profitability while liquidity and firm size do not have a significant effect on profitability.